BRAC Mid term review: Non Formal Education Programme (NFEP), July - August 2001 - BRAC (© BRAC, 2016)
List of Annexes: 1. Term of reference, NFPE III mid term review 2. Itinerary for mid term review mission 3. Documentation consulted 4. Terms of reference, NFPE III mid term review: inputs to the dialogue 5. School observation 6. Field visits to Pabna and Natore 7. BRAC NFPE school observation guidelines 8. BRAC's education programme as of June 2001 9. EDU curriculum group, 10. Education research completed by RED during 1999-2000.